The Use of Analytic Rubric in the Assessment of Writing Performance-Inter-Rater Concordance Study - (:unkn) unknown (EDAM, 2009)
In this study, the purpose was determine whether there was concordance among raters in the assessment of the writing performance using analytic rubric; furthermore, factors affecting the assessment process were examined. The analytic rubric used in the study consists of three sections and ten properties: External structure (format, spelling and punctuation), language and expression (vocabulary, sentences, paragraphs, and expression), organization (title, introduction, story, and conclusion). The basis of the study is composed of narrative texts written by 200 students studying at the sixth and seventh grades of schools located on the Anatolian side of Istanbul (i.e., Beykoz, Kadikoy, Umraniye, and Uskudar). Texts were assessed in accordance with the analytic rubric by six raters. It was determined that the concordance among raters was sufficient according to the results of the assessment.
Keywords: Assessment of Writing Performance; Rubric; Analytic Rubric; Inter-Rater Concordance